PENGARUH KURIKULUM PEMODELAN 3D TERINTEGRASI AI PADA PEMAHAMAN ANAK USIA 10-12 TAHUN DI DIGIKIDZ - Tulkadar, Nur Laila; Riwinoto, Riwinoto (Politeknik Negeri Batam, 2025)
The growing dominance of digital technology presents a significant challenge for the younger generation, who must be well-prepared to face it. Early exposure to digital skills is essential to equip children with the necessary knowledge and capabilities. One such emerging field is 3D modeling, which has seen rapid development in recent years. Through the learning process of 3D modeling, students can enhance their cognitive abilities, creative thinking, and critical problem-solving skills. This study aims to analyze the effectiveness of a 3D modeling curriculum in improving the understanding of children aged 10–12. A comparative approach is used to determine which curriculum demonstrates a higher level of effectiveness. The research employs a mixed-methods approach, combining both qualitative and quantitative data, to obtain more accurate and comprehensive findings.